2022
DOI: 10.55417/fr.2022019
|View full text |Cite
|
Sign up to set email alerts
|

All-Weather, sub-50-cm, Radar-Inertial Positioning

Abstract: Deploying automated ground vehicles beyond the confines of sunny and dry climes will require sub-lane-level positioning techniques that use radio waves, rather than near-visible light radiation. Like human sight, LiDAR and optical cameras perform poorly in low-visibility conditions. We present and demonstrate a novel technique for robust, sub-50-cm, urban ground vehicle positioning based on all-weather sensors. The technique incorporates a computationally-efficient, globally-optimal radar scan registration alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This paper adopts the VDC scheme of Narula et al (2022) with minor modifications to the NHC sideslip model and ZUPT detection mechanism. Details of the VDC scheme are provided in this paper's supplemental material.…”
Section: Vehicle Dynamics Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper adopts the VDC scheme of Narula et al (2022) with minor modifications to the NHC sideslip model and ZUPT detection mechanism. Details of the VDC scheme are provided in this paper's supplemental material.…”
Section: Vehicle Dynamics Constraintsmentioning
confidence: 99%
“…Much automated ground vehicle (AGV) research focuses on the use of lidar and cameras for navigation, but these sensing modalities often perform poorly in low-illumination conditions or during adverse weather such as heavy fog or snowy white-outs. By contrast, positioning techniques based on radio waves, such as automotive radar or GNSS, are robust to poor weather and lighting conditions (Narula et al, 2022). Recent work has found that fusing measurements from low-cost automotive radars with inertial sensing can provide lane-level accuracy in urban environments (Narula et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These solutions are thus not adapted to our use-case of the pipings mapping with a microdrone, which requires a low computational cost in order to maximize battery life and the ability to work in a potentially visually-obstructed environment. Another type of sensor that has recently gained attention in the literature on autonomous navigation is radar, because of its high accuracy and robustness to visually degraded conditions [15]. The main disadvantages of radar are its high power consumption and bulkiness which makes it difficult to embark on a micro-drone.…”
Section: Introductionmentioning
confidence: 99%